Comparison of postoperative analgesia between greater palatine nerve block with local infiltration and local infiltration alone in septoplasty surgeries - Madesh R., Karthik; Sahu, Pankaj Kumar; A. P., Arjun; Vallur, Srujan; Pyadala, Nagababu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Post-operative pain (POP) management is an important factor for the satisfaction after any surgery to patients. The purpose of this study was to evaluate the effect in the post op pain levels by addition of greater palatine nerve block (GPNB) to the local mucosal infiltrative anaesthesia during septoplasty surgery. Methods: A prospective study of 108 patients undergoing septoplasty surgery were divided into 2 groups. Group A with 52 patients and B with 56 patients. Group A received GPNB along with local infiltrative anaesthesia while group B received only the local infiltrative anaesthesia. The POP was studied in them using visual analogue score (VAS) at the 2nd, 5th and 8th post-operative hour. Results: The median VAS of group A at the 2nd, 5th and 8th hour were 2, 2 and 1 respectively while of the group B were 6, 6 and 5 during the same timeline assessment. The decreased POP in group A over B was statistically significant during all the assessments with (p<0.001). The post-operative pain was significantly lesser with no increase in time of surgery, with negligible expenditure and no complications. Conclusions: Greater palatine nerve block can be utilized as an effective addition to septoplasty surgery utilizing the same drug along with local infiltration and give a simple, cost effective and safe addition for a comfortable pain free post op period for a prolonged duration.